2016
DOI: 10.4236/tel.2016.62018
|View full text |Cite
|
Sign up to set email alerts
|

Performance of the Heston’s Stochastic Volatility Model: A Study in Indian Index Options Market

Abstract: This study attempts to analyse one-day-ahead out-of-sample performance of the stochastic volatility model of Heston (SVH) in the Indian context. Also, the study compares the ex-ante performance of the SVH with that of a Two-Scale-Realised-Volatility (TSRV)-based Black-Scholes model (BS) using the liquidity-weighted performance metrics. For the purpose, we utilise the tick-by-tick data of the CNX Nifty index and options thereon, the most liquid equity options in the world in terms of the number of contracts tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…Drawing from extant literature the following potential determinants of the volatility smile are examined: option market-specific variables; variables representing the spot exchange rate dynamics; and a measure of domestic stock market volatility. The intuition for considering these variables is explained here: Time to maturity (T) is measured as the ratio of the number of working days till the option expiry date to total number of working days in the year considered as 252 (Beber, 2008; Sehgal and Vijayakumar, 2008; Singh and Dixit, 2016). Trading days are considered because non-trading days are often ignored by market participants. Following Pena et al (1999), Beber (2008) and Hafner and Wallmeier (2000), the natural log of the number of contracts traded on each sample day (LNCONTR) is used as a proxy for liquidity in the options market. Historical volatility (FXHVOL) is defined as the standard deviation of the daily logarithmic returns of the USDINR exchange rate over a moving window of 20 trading days and annualized considering 252 trading days in a year.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Drawing from extant literature the following potential determinants of the volatility smile are examined: option market-specific variables; variables representing the spot exchange rate dynamics; and a measure of domestic stock market volatility. The intuition for considering these variables is explained here: Time to maturity (T) is measured as the ratio of the number of working days till the option expiry date to total number of working days in the year considered as 252 (Beber, 2008; Sehgal and Vijayakumar, 2008; Singh and Dixit, 2016). Trading days are considered because non-trading days are often ignored by market participants. Following Pena et al (1999), Beber (2008) and Hafner and Wallmeier (2000), the natural log of the number of contracts traded on each sample day (LNCONTR) is used as a proxy for liquidity in the options market. Historical volatility (FXHVOL) is defined as the standard deviation of the daily logarithmic returns of the USDINR exchange rate over a moving window of 20 trading days and annualized considering 252 trading days in a year.…”
Section: Methodsmentioning
confidence: 99%
“…Time to maturity (T) is measured as the ratio of the number of working days till the option expiry date to total number of working days in the year considered as 252 (Beber, 2008; Sehgal and Vijayakumar, 2008; Singh and Dixit, 2016). Trading days are considered because non-trading days are often ignored by market participants.…”
Section: Methodsmentioning
confidence: 99%
“…Singh and Vipul (2015) found mispricing by the BSM model to persist despite the use of a realized volatility measure. Singh and Dixit (2016) found outperformance by the Heston model. All these studies have focused only on the pricing of Indian equity index options.…”
Section: Literature Reviewmentioning
confidence: 93%
“…When taking DVF predictions, we obtain the socalled ad hoc Black-Sholes model (AHBS) [13,14,15]. Quite a few studies found that AHBS approaches outperform much better than classical BS models [16,17].…”
Section: Parametric Modelsmentioning
confidence: 99%
“…where AHBS C is the call option prices under the AHBS model, and IV  is the estimated implied volatility. The AHBS model releases the unrealistic assumption of constant volatility and is able to obtain better performances [16,17].…”
Section: Featuresmentioning
confidence: 99%